Investigating individual trust in semi-virtual collaboration of multicultural and unicultural teams. (September 2016) - Cheng, Xusen; Fu, Shixuan; Sun, Jianshan; Han, Yajing; Shen, Jia; Zarifis, Alex
Abstract: This study aims to investigate individual's trust development for semi-virtual collaboration teams with multicultural and unicultural background. We aim to explore whether the trust levels in multicultural and unicultural semi-virtual groups will be the same, how trust develops over time and what the corresponding factors to the trust development are. In order to answer the questions, a longitudinal case study was conducted in unicultural and multicultural teams. We have taken survey for 144 participants over three stages, as well as interviewed 64 participants. Results of the analysis of the survey data firstly show that no significant difference exists between multicultural and unicultural groups. Then, two factors, collaboration process and clear task help explain this phenomenon. However, the trust development of multicultural groups shows instability and keeps decreasing over time, while unicultural groups behave differently. We found that language, values and habitual behavior lead to the differences in these two types of groups. Highlights: We investigate individual trust development in semi-virtual teams. We compare the multicultural and unicultural teams. A longitudinal case study of semi-virtual teams is conducted. We find some factors leading to the instability of the multicultural teams. It provides clues for future research for trust development in multicultural teams.